Diagnostic potential of WNT signaling gene methylation in pulmonary tuberculosis - Wang, Hua; Wang, Chao-Cai; Huang, Qian; Xiao, Yu; Han, Yin; Xie, Lei; Liu, Yan; Xiong, Yan-Jun (Frontiers in Immunology, 2025)
ObjectivesThe WNT signaling pathway plays important roles in the pathophysiology of pulmonary tuberculosis (PTB). This study aimed to assess the association of the DNA methylation levels of WNT signaling pathway genes and PTB susceptibility, and determine whether the methylation levels might serve as valuable biomarkers for PTB diagnosis.MethodsWe collected blood samples from 98 PTB patients and 96 normal controls, and extracted DNA samples. The methylation levels of promoter region in WNT signaling pathway genes (SFRP1, WNT3A, CTNNB1, WIF-1, DKK-1, LRP5, LRP6) were detected by MethylTarget technique.ResultsWe found that the methylation levels of SFRP1, WNT3A, CTNNB1, DKK-1, LRP6 genes were significantly decreased in the peripheral blood of PTB patients when compared to normal controls, while WIF-1, LRP5 genes methylation levels showed no significant difference between PTB patients and controls. In PTB patients, the increased SFRP1 methylation level was significantly correlated with drug-induced liver injury, pulmonary infection, and the decreased WNT3A, CTNNB1 methylation levels were respectively significantly associated with drug resistance, fever. For diagnosing PTB, the CTNNB1 methylation level demonstrated a relatively higher diagnostic value, achieving an AUC of 0.706. Subsequently, the AUC of WNT3A, DKK-1, LRP6 was 0.660, 0.628, 0.621. The diagnostic value was slightly enhanced when CTNNB1 combined with WNT3A, DKK-1, LRP6, with an AUC of 0.710.ConclusionThe methylation levels of SFRP1, WNT3A, CTNNB1, DKK-1, LRP6 genes were significantly decreased in PTB patients, and single gene or multiple genes methylation panels might serve as potential diagnostic biomarkers for PTB.